Emotion regulation as a mediator on the relationship between emotional awareness and depression in elementary school students - Wang, Ruian; Li, Haoyue; Sang, Biao; Zhao, Yuyang (Frontiers in Psychology, 2023)
Various studies found that emotional awareness plays a fundamental role in emotional intelligence. As a cognitive skill, emotional awareness also has a magnificent effect on the development of individuals’ social adaptation. Most of the previous related studies focused on adults and patients with physical and mental diseases; none focused on children. Therefore, the role of emotional awareness in children’s social adaptation, especially emotional development, remains unclear. While, children in elementary school, especially entering the middle-upper grades, are just beginning their transition from childhood to adolescence, in which emotional adaptation is becoming more apparent to them. Therefore, we sought to determine the significance of EA in children’s emotional . This research adopted both cross-sectional and longitudinal study designs to explore the relationship between emotional awareness and children’s depression, as well as the effect of emotional regulation on this relationship. The sample comprised 166 Chinese elementary school students (89 girls and 77 boys) ranging from 8 to 12 years old. After adjusting for demographic variables (gender, grade, etc.), the results showed that children with high emotional awareness were less likely to adopt expressive suppression as an emotion regulation strategy and had lower depression levels now as well as in the future. In contrast, children with low emotional awareness were more likely to use suppression strategies and showed higher depression levels. Thus, this study suggested that emotional awareness could predict children’s current and future depression statuses. It also revealed that emotional regulation strategies are an important mediating variable explaining the relationship between emotional awareness and children's depression.